The Influence of Sales Growth and Company Size on Tax Avoidance in Manufacturing Companies Listed on The BEI for The Period 2018-2020 - Arifin, syamsul; Anindiyadewi, Nabila Carissa; Nuryadi, Nuryadi; Adhitya Pratama, Devangga Putra; Anisa, Nur Aini (LPPM of NAROTAMA UNIVERSITY, 2025)
This research aimed to analyze the effect of sales growth and firm size against tax avoidance on manufacturing companies registered in BEI for the period 2018-2020. The populations used in this study were 26 food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2020. The sample selected based on the purposive sampling method of 17 companies. The analysis technique used in this research is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and hypothesis testing. The result of the analysis showed that sales growth has no significant effect partially on tax avoidance. This means that the company's sales growth has no effect on tax avoidance. Firm size has a significant negative effect partially on tax avoidance. This means that the larger a company is, the lower the practice of tax avoidance. Meanwhile, sales growth and company size simultaneously have a positive effect on tax avoidance.